A multivariate statistical approaches on physicochemical characteristics of ground water in and around nagapattinam district, cauvery deltaic region of tamil nadu, india (2013)
Ground water samples collected at different locations in and around the Nagapattinam district were analyzed for their physicochemical characteristics. The ground water samples were collected from fifty two dug and deep wells during the monsoon and summer seasons in June and December, 2011. The present investigation is focused on the determination of physico-chemical parameters such as pH, EC, TDS, Ca, Mg, Na, K, HCO3, SO4 and Cl. Ground water suitability for drinking, domestic and agri- cultural purposes was examined by using WHO standards. Correlation, factor and cluster analyses were applied to classify the ground water qualities and to categorize the geochemical processes controlling ground water geochemistry. Factor analysis indicates that seawater intrusion and agriculture runoff are dominant factors controlling the hydrogeochemistry of ground water in the study area. Cluster analysis was helpful for the classification on the basis of contamination characteristics of ground water quality. This study also elucidates that multivariate statistical analyses can be used to improve the understanding of ground water status and assessment of ground water quality. ResumenEn este estudio se analizan las características fisicoquímicas de muestras de aguas subterráneas tomadas en diferentes locaciones en y alrededor del distrito de Nagapattinam. Las muestras se recolectaron en 52 pozos cavados y perforaciones profundas durante las subestaciones del monzón y el verano, en los meses de junio y diciembre (2011). La presente investigación está enfocada en la determinación de parametros fisicoquímicos como pH, EC, TDS, Ca, Mg, Na, K, HCO3, SO4 y Cl. Se examinó la pertinencia de estas aguas para consumo y para irrigación a la luz de los estándares de la Organización Mundial de la Salud. Se aplicaron análisis de correlación, factores y cúmulos para clasificar las muestras y categorizar los procesos geoquímicos que controlan las aguas subterráneas. El análisis de factores indica que la intrusión del agua marina y los vertidos de la agricultura son los principales agentes que intervienen la hidroquí- mica de las aguas subterráneas en el área de estudio. El análisis de cúmulos ayudó a la clasificación de las bases de contaminación características de las aguas subterráneas. Este estudio, además, dilucida que los estudios estadísticos multivariantes pueden ser utilizados para mejorar el conocimiento y la evaluación de la calidad de las aguas subterráneas.